Multiple gingival metastasis of renal cell carcinoma: a case report - Boulanger Lise; Gérard Eric; Curien Rémi (EDP Sciences, 2019)
Introduction: Oral metastases are rare and represent only 1% of malignant diseases of the oral cavity, but they are often associated with poor prognosis. The primary tumor is recognizable in most cases; however, in 27.6% of cases, metastasis is the first clinical manifestation. Observation: An 82-year-old consulted for the recent appearance of a 1-cm-wide gingival tumor on 46. Since this patient had metastatic clear cell renal cell carcinoma, oral metastasis was confirmed by histopathology. In the following weeks, other oral metastases appeared. Palliative radiotherapy was the chosen treatment option, but the patient died before he could benefit from it. Discussion: Multiple oral metastases are rare, and metastasis of renal origin is not the most frequently encountered. The metastatic dissemination pathway described is hematogenous or lymphatic. Diagnosis is often easy if the primary tumor is already identified, but is a challenge if it is not, because the lesion often has a nonspecific appearance. Different surgical, radiotherapeutic, and medical therapeutic options exist, but are often palliative. A new immunotherapy route is under development and looks promising in the treatment of renal cell carcinoma. Conclusions: Oral metastasis often has poor prognosis, and management of the lesion is problematic. However, current research suggests a therapeutic and prognostic improvement.